Management of DNA evidence collected on adolescents in sexual assault investigations: A 10-year review from a large Italian rape centre. (October 2019) - Piccinini, Andrea; Vignali, Giulia; Bailo, Paolo; Barbara, Giussy; Gennari, Giuseppe; Di Candia, Domenico; Albertini, Valentina; Kustermann, Alessandra
Little research is available on the actual forensic use of genetic analyses performed in sexual violence cases, despite their relevant role in legal processes. The present retrospective study aimed to contribute to filling this gap in research, evaluating the actual number of serological/DNA analyses that followed medical examination of female adolescent victims of sexual violence. The study was performed in a large rape centre in Milan (North Italy) by analysing all medical records of female victims of sexual violence aged 13–19 years in the period from January 2006 to December 2015. The total number of sexual assault victims examined aged 13–19 years was 599. In 473 of the cases, biological evidence had been collected. The gathering of biological evidence was accurately performed (double swab technique) in multiple anatomical regions on the victims' bodies, and clothes were acquired when biological stains were present or could be present. Proper handling under chain of custody for all the items collected followed in every case. Despite all of this, serological/DNA analyses were requested in only 9/473 (1.9%) cases. Procedural issues possibly affecting the magistrates' decisions not to use DNA extensively as an investigative tool are also discussed.